Protective Cr coatings with CrN/Cr multilayers for zirconium fuel claddings; Surface and Coatings Technology; Vol. 433 - Sidelev D. V. Dmitry Vladimirovich; Ruchkin S. E. Sergey Evgenjevich; Syrtanov M. S. Maksim Sergeevich; Kashkarov E. B. Egor Borisovich; Shelepov I. A. Igor Alekseevich; Malgin A. G. Aleksandr Gennadjevich; Polunin K. K. Kirill Konstantinovich; Stoykov K. V.; Mokrushin A. A. Andrey Aleksandrovich (2022, 2022)
Title screen